Предмет: Математика,
автор: Saint2999God
Объясните как решается этот пример : 4 * 52 - 4 * (- 95 ) = (- 4) * (- 52 - 95 ) .
Ответы
Автор ответа:
0
4 * 52 - 4 * (- 95 ) =
Выносим за скобку 4. Получаем:
4 * 52 - 4 * (- 95 ) = 4(52-(-95)) = 4(52+95)=4*147=588
Выносим за скобку 4. Получаем:
4 * 52 - 4 * (- 95 ) = 4(52-(-95)) = 4(52+95)=4*147=588
Похожие вопросы
Предмет: Математика,
автор: tasminaz151529
Предмет: Математика,
автор: danial6717
Предмет: Английский язык,
автор: crazyle2829
Предмет: Математика,
автор: УченикДанил
Предмет: Алгебра,
автор: andres19